The Impact of Language Teachers on Vocabulary Mastery: A Retrospective Study Using Blooket: Dampak Guru Bahasa terhadap Penguasaan Kosakata: Sebuah Studi Retrospektif Menggunakan Blooket - Fahmi, Sahal; Purnawan, Ari (Journal of English Teaching and Linguistic Issues (JETLI), 2024)
The focus of teaching strategies used to increase students’ vocabulary understanding has shifted from teaching methods and techniques. Through a retrospective study, the purpose of this research is to observe the strategies employed by educators, particularly the use of the blooket platform to enhance students’ vocabulary mastery. The researcher employed descriptive methodology, qualitative research techniques, and questionnaire design for this study. One of the tools used in research is the Google Form survey. In this study, 10 language teachers at SMA Negeri 1 Imogiri were specifically asked questions about vocabulary. According to the study findings, students’ can increase their vocabulary mastery by utilizing the teachers method of using the blooket platform to teach vocabulary. Students’ will acquire new words more successfully if the teacher uses a wider variety of teaching methods. The next step is to categorize teaching strategies into three groups practice, preparation, and evaluation. Ultimately this study is to provide teachers with useful tools to help them effectively advance their students’ vocabulary mastery